Mouths of rain: An anthology of Black lesbian thought - Jones, Briona Simone (The New Press, 2021)
A groundbreaking collection tracing the history of intellectual thought by Black Lesbian writers, in the tradition of The New Press’s perennial seller Words of Fire “Briona Simone Jones’s anthology Mouths of Rain is an audacious, unapologetic, transgressive collection of Black ‘queer’ writing across genre, time, identity, age, and political leanings. This sister/companion to Words of Fire, published thirty years ago, makes visible—again—our passionate and unwavering commitments to the eradication of all oppressions. It bears witness to the necessity and power of the field of Black Lesbian Studies and is a love offering to us all.” —Beverly Guy-Sheftall, Anna Julia Cooper Professor of Women’s Studies at Spelman College and editor of Words of Fire: An Anthology of African-American Feminist Thought Winner, Publishing Triangle’s Judy Grahn Award for Lesbian Nonfiction Winner, Lambda Literary Award in LGBTQ Anthology African American lesbian writers and theorists have made extraordinary contributions to feminist theory, activism, and writing. Mouths of Rain, the companion anthology to Beverly Guy-Sheftall’s classic Words of Fire, traces the long history of intellectual thought produced by Black Lesbian writers, spanning the nineteenth century through the twenty-first century. Using “Black Lesbian” as a capacious signifier, Mouths of Rain includes writing by Black women who have shared intimate and loving relationships with other women, as well as Black women who see bonding as mutual, Black women who have self-identified as lesbian, Black women who have written about Black Lesbians, and Black women who theorize about and see the word lesbian as a political descriptor that disrupts and critiques capitalism, heterosexism, and heteropatriarchy. Taking its title from a poem by Audre Lorde, Mouths of Rain addresses pervasive issues such as misogynoir and anti-blackness while also attending to love, romance, “coming out,” and the erotic
http://public.eblib.com/choice/PublicFullRecord.aspx?p=6026213
Keywords: anthologie; approches et analyses; hétérosexisme; identités LGBTQIA2+; misogynoir; outils; ouvrages de références; queer; racisme; ressource en ligne; systèmes d'oppressions

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice–one of the most important and ground-breaking subjects to have emerged in philosophy in recent years–refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Le chap 10 de Patricia Hill Collins, “Intersectionality and Epistemic Injustice” a été donné en lcture au cours FEM9000. Le chap 14 de Kim Hall, “Queer Epistemology and Epistemic Injustice” a été donné en lecture au cours FEM9000. Le chap 15 de Rachel McKinnon, “Allies behaving badly: Gaslighting as epistemic injustice” a été donné en lecture au cours FEM9000. Le chap 16 de Shelley Tremain, “Knowing Disability Differently” a été donné au cours FEM9000. Le chap 33 de Anastasia Scrutton, “Epistemic Injustice and Mental Illness” a été donné en lecture au cours FEM9000. Le chap 34 de Rebecca Tsosie, “Indigenous peoples, anthropology, and the legacy of epistemic injustice” a été donné au cours FEM9000.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
https://uqam-bib.on.worldcat.org/oclc/953804743
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Queer inclusion in teacher education: Bridging theory, research, and practice - Murray, Olivia J. (Routledge, 2015)
Queer Inclusion in Teacher Education explores the challenges and promises of building queer inclusive pedagogy and curriculum into teacher education. Weaving together theory, research findings, and practical "how-to" strategies and materials, it fills an important gap by offering a clear roadmap and resources for influencing the knowledge, beliefs, and actions of faculty working with pre-service teachers. While the book has implications for policy change, most immediately, readers will feel empowered with ideas for faculty development they can implement in their own teacher education programs. Looking at both the politics and practices of teacher education and the ways in which queer issues manifest in schools, it is hopeful in suggesting that if teachers and pre-service teachers can critically reflect on homophobia and heteronormativity, they can begin to think about and relate to queer youth in a different, more positive and inclusive way. A Companion Website [http://queerinclusion.com] with additional activities and materials for teacher educators and faculty development and a practical guide enhances the usefulness of the book.
Keywords: LGBTQIA2+; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; outils; ouvrages de références; pédagogie; pédagogie queer; queer; sciences de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques